USM RESTRUCTURES INTERNATIONAL OFFICE – PROMOTES STUDENT MARKETABILITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 27 February 2016 Universiti Sains Malaysia (USM) is restructuring and rebranding its International Office (IO) to become the International Mobility and Career Centre (IMCC) beginning this year.